PELANGGARAN STRUKTUR PERCAKAPAN DALAM ACARA MATA NAJWA DI TRANS7 - Nina Puspita Dewi Setianingrum; Rahayu Pujiastuti (Universitas PGRI Adi Buana Surabaya, 2018)
Najwa's eye is a show on Trans7 aired every Wednesday at 20:00 pm. Every week the topic of discussion in the Najwa Eye event varies. One of the topics of discussion taken this week on the 100 Days of the Anis-Password, because the news about the performance of Anis-Sandi is warmly discussed among the public. There are many violations encountered regarding the conversational structure contained in the Najwa Eye event. Based on this research, this study aims to find out two things, namely (1) violation of the structure of the conversation and (2) the purpose of the violation is done.Researchers use a qualitative approach. This research data in the form of conversation that contains violation of conversation structure in Mata Najwa event. Sources of data in this research in the form of document data written Mata Najwa with 100 Days Anis-Sandi topic. Technique of collecting data is done by documentation. Data analysis techniques used are identification, data grouping, interpretation, and draw conclusions.Based on the result of the research, it can be concluded that (1) Violation of conversation structure in the Najwa Eye event there are two violations, namely the turn-taking and the adjacency pairs. (2) The purpose of violation of the structure of the conversation in the Najwa Eye event, ie to explain in detail, to get the attention of the speech partner, to maintain the continuity of the speech so as not to stop, and to bring up a new, different but still in one discussion.